Über wenig bekannte Zwergspinnen aus den Alpen - V (Arachnida: Aranei, Erigonidae). - Thaler, Konrad (Contributions to Entomology = Beiträge zur Entomologie, 1978)
New localities from the Eastern Alps and brief habitat records are given for 7 spp., most of them being new for the Austrian fauna: Cochlembolus clavatus (Schenkel), Diplocephalus protuberans (O. P. Cambridge) (male female; female compared with D. helleri (L. Koch), Erigone cristatipalpus Simon (male (m), female (f); compared with E. tirolensis L. Koch), Milleriana inerrans (O. P. Cambridge), Oedothorax gibbifer (Kulczynski) (m), Ostearius melanopypius (O. P. Cambridge) (m) Troxochrus nasutus Schenkel. 3 further spp. are discussed more broadly: Astenargus perforatus Schenkel (m characterized for first time), Silometopus braunianus spec. nov. (locus typicus Prov. Brescia, Valtellina 2000; m,f; a key to the males of the genus being included), Walckenaera languida (Simon) (m,f; differentiated from W. cucullata (C. L. Koch). Finally, the 31 species of Erigonidae described since 1900 from Switzerland and Austria (authors: Lessert 6, Schenkel 16, Vogelsanger 1, Kritzcher 1, Wunderlich 3, Thaler 4) are discussed and summarized. There are 2 species inquirendae (Brachycentrum (?) tenerum Schenkel, Panamomops (?) similis Schenkel), 18 species are regarded as valid (4 of them still being known one sex only), 11 as junior synonyms. Nomenclatural Acts braunianus Thale, 1978 (Silometopus), spec. n.